Pendampingan Pembelajaran Bahasa Inggris Melalui Media Online di masa Pandemi Covid-19 Di Pondok Pesantren Tahfidzul Qur’an Mojo Kediri - Vaizatul Wafa’; Muhammad Al Faruq (LP3M IAIFA Kediri, 2020)
In Indonesia English is a foreign language to learn. But not a few also the Education system in pesantren implements a mandatory system of both Arabic and English. In practice both teachers and students still face various problems when the learning process. Various responses can be found in the classroom related to these problems, especially in the current learning system through online methods due to the Covid-19 pandemic. The difficulties faced in online learning methods are very clearly seen, especially the attitude of santri during the learning process, as well as active participation in learning. This research aims to explain the difficulties faced by students in learning English and its causative factors. The study used a qualitative approach with observations, photographs and video footage. Analysis of research data is done through. The results showed that the study subjects had difficulty learning English that varied with varying degrees of difficulty. This occurs due to different levels of English mastery factors and lack of qualified assistance.